Malaysian cocoa market modeling: A combination of econometric and system dynamics approach - Applanaidu, Shri Dewi; Mohamed Arshad, Fatimah; Abdel Hameed, Amna Awad; Hasanov, Akram; Idris, Nurjihan; Abdullah, Amin Mahir; Shamsudin, Mad Nasir (2009)
The Malaysian cocoa sector has undergone dramatic changes during the last few decades.In the early years of 1970s, this sector has maintained an upward trend in the area and consequently the production.However, the trend reversed in the late 1980s due to factors such as declining world prices, higher labour costs, widespread of cocoa pod diseases and the pull of more lucrative crops (in particular palm oil).By 2008 only about 19,976 hectares were planted with cocoa compared to a peak of 414,236 ha in 1989.Production of cocoa beans has trended down accordingly.The study combines the econometric and system dynamics approach in modeling the Malaysian cocoa market.A first order system was developed to capture the interdependencies of the major structural elements of the markets such as production, local and export demands, inventory and imports.Nevertheless, the model provides an understanding of the interrelationships between the system components and allows the simulation of policy variables changes.Future work will involve a detail examination of the interaction cocoa supply chain system (from farm to export) to provide a much more comprehensive representations of the dynamics of the market.